PTH-080 Clostridium difficile infection in pre-existing inflammatory bowel disease: a case series. Issue 2 (June 2019) - Campbell, Iona; Brownson, Emily; Robertson, Elaine
Abstract : Introduction: Inflammatory bowel disease (IBD) is a risk factor for clostridium difficile infection (CDI), and It is known that CDI in an IBD patient is associated with higher morbidity and mortality. It is thought that factors including alterations in the gut microbiome, mucosal disruption and immunosuppression provide a synergistic environment for CDI to complicate an IBD flare, yet there is no agreed consensus on best management of these patients. Our aim is to examine a series of recent cases to assess our own practice and subsequent outcomes. Methods: A retrospective analysis was carried out of all cases of CDI in IBD patients in NHS GG&C during 2018. Patients were identified via the regional CDI database; those with co-existing IBD were extrapolated. Data collected included demographics, IBD subtype, and presence of other CDI risk factors. Severity of symptoms was assessed using Truelove & Witts Criteria. Initial management, and any changes following the diagnosis of CDI were noted. Outcomes were measured by length of stay, survival to discharge and whether surgical intervention was required. Results: 14 patients in total were identified. 10 had a diagnosis of ulcerative colitis, 3 of Crohn's disease and 1 IBD unclassified. 11 of the 14 were on immunosuppressive therapy at the time of CDI (2 anti TNF; 1 thiopurine; 1 steroid; 7 5ASA) – this was continued in all cases. 9 of the patients presented with acute severe colitis based on Truelove & Witts Criteria. Once the diagnosis of CDI was established metronidazole was given in 9 cases, and vancomycin in 5 (doses and any subsequent alterations shown in table 1 ). Assessment with Travis criteria on day 3 indicated high chance of colectomy in 7 patients however none required surgical intervention. No patients received rescue biologics or faecal transplant. Median length of stay was 19 days (range 3–169). One patient did not survive to discharge. Since index admission 4 were readmitted, and 6 have subsequently had their IBD therapy escalated. Conclusions: Managing CDI in those with co-existing IBD is clinically challenging. This case series highlights the lack of consensus on how this should be approached, even within a single health board. This suggests that a wider body of work is required to establish guidance and provide better outcomes.